Teachers' Union Power in a Budget Crunch: Lasting Ramifications of Differential Spending Responses to the Great Recession. Issue 2 (March 2022) - Swain, Walker A.; Redding, Christopher
In the wake of the 2007 housing crash and subsequent economic recession, state legislatures across the country faced substantial declines in revenues, and by 2011, for the first time in more than a decade, average spending on education declined. However, states' budgetary responses to the Great Recession were decidedly uneven, with some making lasting cuts to public education. This article uses longitudinal data on state-level educational spending, politics, demographics, economic well-being, and a unique set of union strength indicators to assess the strength of teachers' unions as advocates for education spending by examining their role in states' varied budgetary responses to the Great Recession. We find that states with laws prohibiting collective bargaining for teachers and states with lower union dues per teacher made substantially larger cuts to overall educational expenditures, even after controlling for time-invariant state characteristics, secular trends, and an extensive set of time-variant state-level covariates.